ANALISIS HUBUNGAN DESENTRALISASI, KETERSEDIAAN PELAYANAN KESEHATAN DAN KESEHATAN IBU DAN ANAK DI INDONESIA 2018 - Rizky Maulidya (Jurnal Administrasi Publik, 2023)
Analysis of Decentralization Relations, Availability of Maternal and Child Health and Health Services in Indonesia 2018. This study aims to analyze empirically the relationship between decentralization, the availability of health services and maternal and child health at the district/city level in Indonesia in 2018. The statistical analysis method used is Moran's I which is used to detect the existence of a spatial relationship in each variable, and SEM-PLS which is used to determine the relationship between variables. The results of this study are that there is a positive spatial autocorrelation in the variables of decentralization, availability of health services, and maternal and child health at the district/city level in Indonesia. District/city decentralization has no direct influence on maternal and child health outcomes. Decentralization will only be able to significantly improve maternal and child health outcomes if the districts/cities can increase the availability of health services. Improving decentralization, by optimizing regional revenues through taxes, is important to do to increase the availability of health services, so that better maternal and child health can be achieved.